Bioactive silicon-based dental gel associated with a calcium booster for dentin hypersensitivity treatment: A randomized clinical study - Fernandes, Leandro Araújo; Reis, Ana Luíza Marques; de Cássia dos Reis, Marcela; Mazzola, Thamires; da Cruz Pegoraro, João Vitor; Neto, Sebastião Orestes Pereira; de Lima, Daniela Coelho; D’Alpino, Paulo Henrique Perlatti [UNESP] (Medicina Oral, S.L., 2024)
Background: Dentin hypersensitivity affects a significant portion of the world’s population, causing pain and negatively impacting oral health and quality of life This clinical study investigated the effectiveness of a desensitizing fluoride silicon-rich dental gel associated with a calcium booster. Material and Methods: In this single-blind, randomized, parallel-group clinical trial, forty-eight volunteers diagnosed with dentin hypersensitivity and qualified to participate were randomized into 2 groups: (1) fluoride silicon-rich dental gel (REFX Technology)/calcium booster (Si/Ca protocol); (2) Pumice stone diluted in saline. A draw was carried out between the right and left sides of the patients so that either a prophylaxis with the dental gel associated with calcium or with fine pumice stone diluted in saline was carried out. An evaporative test was used to check for dentin hypersensitivity in the subjects before and immediately after treatment and scored using the Schiff scale, rated 0 to 3. Data were statistically analyzed (ANOVA/Tukey test, α=5%). Results: The treatment with Si/Ca protocol drastically reduced dentin hypersensitivity (from 2.58 to 0.67) immediately after the use. In the control group (Pumice stone), similar results were observed before and after treatment (2.67 and 2.82, respectively). Conclusions: The Si/Ca protocol was fast and effective in reducing pain caused by dentin hypersensitivity.
Keywords: Clinical trial; dentin hypersensitivity; desensitizing; toothpaste